The anti-leukemia activity and mechanisms of shikonin: a mini review - Dong, Han; Chang, Chun-Di; Gao, Fei; Zhang, Na; Yan, Xing-Jian; Wu, Xue; Wang, Yue-Hui (Frontiers in Pharmacology, 2023)
Leukemia encompasses a group of highly heterogeneous diseases that pose a serious threat to human health. The long-term outcome of patients with leukemia still needs to be improved and new effective therapeutic strategies continue to be an unmet clinical need. Shikonin (SHK) is a naphthoquinone derivative that shows multiple biological function includes anti-tumor, anti-inflammatory, and anti-allergic effects.Numerous studies have reported the anti-leukemia activity of SHK during the last three decades and there are studies showing that SHK is particularly effective towards various leukemia cells compared to solid tumors. In this review, we will discuss the anti-leukemia effect of SHK and summarize the underlying mechanisms.Therefore, SHK may be a promising agent to be developed as an anti-leukemia drug.